THE EDITORIAL DIVISION IN KOMPAS GRAMEDIA BRANCH OF YOGYAKARTA - , FATIMAH NUGRAHENI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This Graduating Paper aims to explain the editorial division in Kompas newspaper and outlines the work of each section and also working procedures in the editorial division . The structure and level of the editorial process and works are also included in this Graduating Paper . An explanation of the challenges and opportunities in the development of future Kompas newspaper is also described herein . Furthermore , this paper is expected to give contribution to the students , especially students of English Diploma Sekolah Vokasi UGM, in providing additional information about Kompas Editorial Division and also about how to work as a journalist at the newspaper . The method of data collection was done by direct observation , interviews , and literature study. Direct observation was conducted for 2 months in order to figure out how to work technically in editorial division . Interviews with reporters and staff are done to obtain data and information about Kompas newspaper editorial division. Literature study is conducted to gather background information in the discussion of this Graduating Paper . Based on direct observation and interviews, editor of Kompas newspaper division is the division that is very important in terms of the success of its article. Kompas newspaper has always had the technique in terms of an effective news coverage, writing articles directly at the field, as well as the data are always informative and accurate. The problems that exist in Kompas are the lack of members and also the general problem of the freedom of the press. Kompas newspaper editorial division can be said as the important role of the entire contents of Kompas newspaper.